Linguagem e tecnologia: experiências na educação infantil - Figueiró, Carolina Budaszewski (Universidade do Vale do Rio dos Sinos, 2018)
Through a bibliographical review, this article search to problematize the relation between the child's experience in language acquisition and their learning processes through this experience, with the digital culture in which your children are currently inserted. Firstly, contextualizing the importance of experience in the learning process, then the process of language acquisition as a means of expressing thought in different forms, mainly through the graphic language and rescuing concepts about the fields of experience, where playfulness and the production of meaning are related to the experience and the child´s experience. In this way, the relation of the use of digital technologies in children's early childhood education, allows a more meaningful learning, making this process more playful and integrative with the present, since our children are already born inserted in this digital culture.
Keywords: Linguagem; Experiência; Tecnologia; Marcas gráficas; Langage; Experience; Technology; Graphic brands